Fundamental Changes in Soil Taxonomy. Issue 4 (24th July 2015) - Stolt, Mark H.; Needelman, Brian A.
Abstract : Soil Taxonomy has become increasingly complex during the past 50 yr, and the number of taxa has grown almost exponentially. This complexity detracts from the ability of Soil Taxonomy to serve the needs of increasingly diverse users. We review the objectives of Soil Taxonomy, discuss current issues with applying Soil Taxonomy, and present some suggested changes meant to initiate an open discussion on making fundamental changes. Our goal is to develop a dialog among the scientific community that will lead to a revised document that has not lost the critical details we require but can meet the objectives of our system of soil classification by being a document relevant to the breadth of potential users. We are not proposing changes to the general architecture of Soil Taxonomy, but rather suggesting fundamental changes in definitions, criteria, concepts, and format (what is emphasized within each category). These potential changes may be moderate, extensive, or conceptual. Example changes include simplifying the definition of organic soil materials (moderate change), moving moisture regime from the suborder to the family level (extensive change), and harmonizing meanings across the hierarchy (conceptual change). We believe that purposeful and well‐designed changes to Soil Taxonomy have the potential to create a system that is less complicated, is more user friendly, and that can serve as an effective and engaging tool for the soil science community to reach other disciplines and communities that use soils information.